A relação pedagógica e o enfrentamento dos conflitos e das violências na escola - Bordin, Márcia Simone da Silva (2012)
The current paper is linked to the research line: School Practices and Public Policies of the Post-graduation Program on Education (PPGE) at the Federal University of Santa Maria. This investigation, which theme is the pedagogical relation, the conflicts and violence in schools, is part of the research group Moral Affection , and its main project: The conflicts and the sentiments present in the pedagogical relation and the interrelations in the building of moral personality. The objective of this research was to investigate whether the way the pedagogical relations are worked in the classroom benefits or not the act of facing the violence in schools. To do so, some classes of Physical Education of the fifth grade (research participants), in Fundamental school in Santa Maria, Rio Grande do Sul state, were observed. The sort of research used was the Case Study with a qualitative approach. The investigation instruments were: direct observation, semi-structured interview and a questionnaire. The data analysis happened under the theoretical support of the following authors: pedagogical relation and its conditions: the knowledge (ESTRELA, 1994), activities (ESTRELA, 1994; ASSIS, 2003); the rules (DE VRIES, ZAN, 2003; VINHA, 2003); violence acts (MORAIS, 1995); conflicts (VINYAMATA, 2005). Based on the data analysis, it was observed that the teacher s pedagogical practice helped somehow to face the conflicts and violence. However, it could intensified the idea of making the students participate and know their value in making and modifying the rules.